Microglial autophagy in Alzheimer’s disease and Parkinson’s disease - Wang, Zhifu; Wang, Qi; Li, Shihua; Li, Xiao-Jiang; Yang, Weili; He, Dajian (Frontiers in Aging Neuroscience, 2023)
Alzheimer’s disease (AD) and Parkinson’s disease (PD) are the most common neurodegenerative diseases, characterized by gradual and selective loss of neurons in the central nervous system. They affect more than 50 million people worldwide, and their incidence increases with age. Although most cases of AD and PD are sporadic, some are caused by genetic mutations that are inherited. Both sporadic and familial cases display complex neuropathology and represent the most perplexing neurological disorders. Because of the undefined pathogenesis and complex clinical manifestations, there is still no effective treatment for both AD and PD. Understanding the pathogenesis of these important neurodegenerative diseases is important for developing successful therapies. Increasing evidence suggests that microglia-mediated neuroinflammation is associated with the pathogenesis of AD and PD, and its dysfunction has been implicated in disease progression. In this review, we focus on the autophagy function in microglia and its dysfunction in AD and PD disease models in an attempt to help our understanding of the pathogenesis and identifying new therapeutic targets of AD and PD.